Answer:
So, solution of the differential equation is
![y(t)=-\frac{5x^2}{4}\cot 2x\cdot \cos 2x+c_1e^{-2it}+c_2e^{2it}\\](https://tex.z-dn.net/?f=y%28t%29%3D-%5Cfrac%7B5x%5E2%7D%7B4%7D%5Ccot%202x%5Ccdot%20%5Ccos%20%202x%2Bc_1e%5E%7B-2it%7D%2Bc_2e%5E%7B2it%7D%5C%5C)
Step-by-step explanation:
We have the given differential equation: y′′+4y=5xcos(2x)
We use the Method of Undetermined Coefficients.
We first solve the homogeneous differential equation y′′+4y=0.
![y''+4y=0\\\\r^2+4=0\\\\r=\pm2i\\\\](https://tex.z-dn.net/?f=y%27%27%2B4y%3D0%5C%5C%5C%5Cr%5E2%2B4%3D0%5C%5C%5C%5Cr%3D%5Cpm2i%5C%5C%5C%5C)
It is a homogeneous solution:
![y_h(t)=c_1e^{-2i t}+c_2e^{2i t}](https://tex.z-dn.net/?f=y_h%28t%29%3Dc_1e%5E%7B-2i%20t%7D%2Bc_2e%5E%7B2i%20t%7D)
Now, we finding a particular solution.
![y_p(t)=A5x\cos 2x\\\\y'_p(t)=A5\cos 2x-A10x\sin 2x\\\\y''_p(t)=-A20\sin 2x-A20x\cos 2x\\\\\\\implies y''+4y=5x\cos 2x\\\\-A20\sin 2x-A20x\cos 2x+4\cdot A5x\cos 2x=5x\cos 2x\\\\-A20\sin 2x=5x\cos 2x\\\\A=-\frac{x}{4} \cot 2x\\](https://tex.z-dn.net/?f=y_p%28t%29%3DA5x%5Ccos%202x%5C%5C%5C%5Cy%27_p%28t%29%3DA5%5Ccos%202x-A10x%5Csin%202x%5C%5C%5C%5Cy%27%27_p%28t%29%3D-A20%5Csin%202x-A20x%5Ccos%202x%5C%5C%5C%5C%5C%5C%5Cimplies%20y%27%27%2B4y%3D5x%5Ccos%202x%5C%5C%5C%5C-A20%5Csin%202x-A20x%5Ccos%202x%2B4%5Ccdot%20A5x%5Ccos%202x%3D5x%5Ccos%202x%5C%5C%5C%5C-A20%5Csin%202x%3D5x%5Ccos%202x%5C%5C%5C%5CA%3D-%5Cfrac%7Bx%7D%7B4%7D%20%5Ccot%202x%5C%5C)
we get
![y_p(t)=A5\cos 2x\\\\y_p(t)=-\frac{5x^2}{4}\cot 2x\cdot \cos 2x\\\\\\y(t)=y_p(t)+y_h(t)\\\\y(t)=-\frac{5x^2}{4}\cot 2x\cdot \cos 2x+c_1e^{-2it}+c_2e^{2it}\\](https://tex.z-dn.net/?f=y_p%28t%29%3DA5%5Ccos%202x%5C%5C%5C%5Cy_p%28t%29%3D-%5Cfrac%7B5x%5E2%7D%7B4%7D%5Ccot%202x%5Ccdot%20%5Ccos%20%202x%5C%5C%5C%5C%5C%5Cy%28t%29%3Dy_p%28t%29%2By_h%28t%29%5C%5C%5C%5Cy%28t%29%3D-%5Cfrac%7B5x%5E2%7D%7B4%7D%5Ccot%202x%5Ccdot%20%5Ccos%20%202x%2Bc_1e%5E%7B-2it%7D%2Bc_2e%5E%7B2it%7D%5C%5C)
So, solution of the differential equation is
![y(t)=-\frac{5x^2}{4}\cot 2x\cdot \cos 2x+c_1e^{-2it}+c_2e^{2it}\\](https://tex.z-dn.net/?f=y%28t%29%3D-%5Cfrac%7B5x%5E2%7D%7B4%7D%5Ccot%202x%5Ccdot%20%5Ccos%20%202x%2Bc_1e%5E%7B-2it%7D%2Bc_2e%5E%7B2it%7D%5C%5C)
Answer:
$150
Step-by-step explanation:
Erick has to pay $15 per month so for 5 months he will have to pay $75 because 15 times 5 is 75. So $75 for registration fee + $75 for 5 months to use the gym give us $150
Answer: the length of Maria's piece of string is 45 inches.
the length of Katy's piece of string is 39 inches
Step-by-step explanation:
Let x represent the length of Maria's piece of string.
Let y represent the length of Katy's piece of string.
When they put the two pieces of string together end to end, the total length is 84inches. This means that
x + y = 84 - - - - - - - - - - - -1
Maria's string is 6 inches longer than Katy's. This means that
x = y + 6
Substituting x = y + 6 into equation 1, it becomes
y + 6 + y = 84
2y + 6 = 84
2y = 84 - 6 = 78
y = 78/2 = 39
x = y + 6 = 39 + 6
x = 45
Answer:
15x+25
Step-by-step explanation:
cancel out (2x+1) you'll be left with 5(3x+5)
when multiply 5 by 3x+5